Effectiveness and life-cycle cost-benefit analysis of active cold storages for building demand management for smart grid applications. (1st June 2015) - Cui, Borui; Gao, Dian-ce; Wang, Shengwei; Xue, Xue
Highlights: A fast power demand response strategy involving cold storages is presented. Immediate and significant power demand reduction can be provided by the strategy. The life-cycle cost saving potential of cold active storage is analyzed. Small scale active storages can offer significant life-cycle cost saving. Abstract: A fast power demand response (DR) strategy involving both active and passive cold storages is presented. This control strategy provides an immediate and stepped power demand reduction through shutting chiller(s) down when requested. The results show that the power demand reduction and building indoor temperature during the DR event can be predicted accurately. The power demand reduction is stable which is more predictable for the grid management. The building indoor temperature rise is restrained and indoor thermal comfort is improved through use of a small scale active storage system during the DR event. The incentive bought by an existing DR program is used to calculate the economic benefit of the demand reduction controlled by the developed fast DR strategy. In addition, an electricity price structure in South China is introduced to calculate the cost saving potentials of the active storages, when a storage-priority control is used to shift peak demand in normal days. The results show that small scale active storages can also offer significant life-cycle cost saving for building demand management.